Implications of early selection for grain colour on iron and zinc content and productivity of common bean. Issue 2 (15th January 2015) - Teixeira, Rita de Kássia Siqueira; Lima, Dayane Cristina; Abreu, Ângela de Fátima Barbosa; Ramalho, Magno Antonio Patto; Link, W.
Abstract Brazilian consumers prefer beans of the beige grain colour. Common beans help supply dietary requirements for iron and zinc. The objectives of this study were (i) to determine whether early selection for grain colour affects the iron and zinc content and the grain yield in common beans and (ii) if an association between these characteristics was found, to obtain lines of carioca‐type grains with a high iron and zinc content and good grain yield. We evaluated 96 F3:4, F3:5 and F3:6 progeny at two locations for iron and zinc content and grain yield. We selected 48 progeny for grain colour and chose 48 others at random. We found that early selection for grain colour does not affect the zinc content and grain yield. A positive and high association was found between iron and zinc content, and both iron and zinc content were slightly negatively correlated with grain yield. It is possible to obtain common bean lines combining a high iron and zinc content with good grain yield as long as a selection index is used.